Ultra-fast rate capability of a symmetric supercapacitor with a hierarchical Co3O4 nanowire/nanoflower hybrid structure in non-aqueous electrolyte1. Issue 17 (27th February 2015) - Padmanathan, N.; Selladurai, S.; Razeeb, Kafil M.
<x xml:space="preserve">Abstract</x> A free standing Co3O4 nanowire/nanoflower hybrid structure on flexible carbon fibre cloth (CFC) was designed via a facile hydrothermal approach followed by thermal treatment in air.